O retrofit sustentável como uma estratégia para a reabilitação consciente do patrimônio cultural arquitetônico - Gaspary, Fernanda Peron (2012)
This dissertation constitute a reflection on the sustainable Retrofit as a conscious strategy to rehabilitate the architectural cultural heritage. In this context, the concept of Retrofit is explored and associated with various dimensions of sustainable development. This research also reviewed aspects relating to diversities and similarities between models of interventions. The methodology accommodated bibliographic search, consultation on regulatory agencies of brazilian constructions, theoretical-historical survey and direct observation on case study of a building of historic heritage, the Museu do Pão, located at the top of the Vale do Taquari, RS. In this case study, the Retrofit was analyzed from Brazilian Association of Technical Standards to a broader perspective on research. The results seems to evidence that are other sustainable development variables were detected after the Retrofit in addition to the environmental dimension. These dimensions are the cultural, social, and economic. These results may help explain the emphasis term's sustainable Retrofit on architectural cultural heritage.